Sajameh Pemanfaatan Limbah Organik di BSU (Bank Sampah Unit) Sajameh untuk Pembuatan Kompos dan Budidaya Maggot: “Pemberdayaan Masyarakat dalam Pengelolaan Sampah Organik melalui Budidaya Maggot dan Produksi Kompos” - Ade Rakhmadi; Ely Vebriyanti; Mirzah Mirzah; Indri Juliyarsi; Sri Melia; Rizki Dwi Setiawan; Aronal Aronal; Afriani Sandra; Ade Sukma; Deni Novia; Montesqrit Montesqrit; Ferry Lismanto Syaiful; Adilla Fitri; Lara Suci (LPPM Universitas Andalas, 2026)
Organic household and fish waste management remains a significant environmental challenge in coastal communities, where inadequate waste treatment contributes to environmental pollution and the underutilization of valuable organic resources. Although EM4-based composting and Black Soldier Fly (BSF; Hermetia illucens) bioconversion have been widely adopted as separate waste management technologies, their integration into a community-based waste management system has rarely been implemented or systematically documented in Indonesian coastal communities. This program aimed to evaluate the effectiveness of integrating EM4-based composting with BSF cultivation in enhancing community capacity and promoting sustainable organic waste management at the Sajameh Waste Bank in Bungus, Padang, Indonesia. The program adopted a Participatory Action Research (PAR) approach using a one-group pretest-posttest design involving 30 participants. Program activities included needs assessment, community education, hands-on training in composting and BSF cultivation, continuous mentoring, and evaluation through questionnaires, direct observation, and comparative analyses of pretest and posttest scores. The program increased participants' knowledge by 65%, achieved an 80% community participation rate, produced approximately 50 kg of compost per month during the initial implementation phase, and generated strong interest in BSF cultivation among 70% of participants. In addition, an independent community group was established to sustain waste management activities beyond the program period. These findings demonstrate that integrating EM4-based composting with BSF bioconversion effectively enhances community capacity while supporting environmentally sustainable organic waste management. This integrated community-based approach offers a practical and potentially scalable model for improving organic waste utilization and advancing sustainable waste management practices in coastal communities.